The Role of Knowledge Management in Corporate Entrepreneurship Through Innovation and Research & Development - Amiri, Fataneh; Kasrai, Ahmadreza; Kabaranzad Ghadim, Mohamadreza (Management Strategies and Engineering Sciences, 2025)
Corporate entrepreneurship is an entrepreneurial process that organizations undergo to enable all employees to function as entrepreneurs, allowing them to continuously, swiftly, and efficiently carry out individual or group activities within the central organization. In this context, knowledge management, innovation, and research and development (R&D) processes can be influential. This study aims to examine the role of knowledge management in corporate entrepreneurship through innovation and R&D. To achieve this, a review of the theoretical literature was first conducted to establish the research framework. Based on this framework, a conceptual model was formulated, and research hypotheses were developed. To test the research hypotheses, the statistical population consisted of managers and experts from a knowledge-based company operating in the oil and gas sector, with a total of 56 individuals. Since no sampling was conducted, the questionnaire was distributed among all personnel. The questions in the questionnaire were adapted from reliable sources, and their validity and reliability were confirmed. Given the non-normal distribution of the data, the partial least squares (PLS) method and Smart PLS 2 software were employed for statistical analysis. Based on the significance values related to the hypotheses, all five hypotheses were confirmed. The effect of knowledge management on R&D was found to be 0.816, the effect of knowledge management on corporate entrepreneurship was 0.842, the effect of knowledge management on innovation was 0.881, the effect of R&D on corporate entrepreneurship was 0.874, and the effect of innovation on corporate entrepreneurship was 0.825. The findings of this study indicate that knowledge management can influence not only corporate entrepreneurship but also innovation and R&D. Furthermore, innovation and R&D can contribute to enhancing corporate entrepreneurship. Considering the components and indicators of each of these variables can help improve three dimensions: innovation, the development of new products and services, or risky processes, ultimately impacting performance.